Analisis pengaruh kualitas institusi dan FDI terhadap pertumbuhan ekonomi di negara ASEAN - Hanan, Vaniandra; Prastowo, Prastowo (Jurnal Kebijakan Ekonomi dan Keuangan, 2025)
Purpose – This research aims to analyze the influence of institutional quality and FDI on economic growth in ASEAN countries. Methods – The method used in this research is panel data regression using economic growth research variables namely GDP per capita, FDI and institutional quality measured through 6 indicators based on world government indicators including Control of Corruption (CC), Voice and Accountability (VA), Government Effectiveness (GE), Rule of Law (ROL), Political Stability (PS), Regulatory Quality (RQ) are sourced from the World Bank. Findings – The research results show that Regulatory quality, Control of corruption, Voice and accountability, and Government effectiveness have a significant effect on economic growth in ASEAN countries. Apart from that, FDI also has a significant influence on economic growth in ASEAN countries. Implication – The government improves the quality of institutions and ease of investment to increase economic growth. Originality – This research contributes to economic development policies related to economic institutions and investment. Abstrak Tujuan – Penelitian ini bertujuan untuk menganalisis pengaruh kualitas institusi dan FDI terhadap pertumbuhan ekonomi di negara ASEAN. Metode – Metode yang digunakan dalam penelitian ini adalah regresi panel data dengan menggunakan variabel penelitian pertumbuhan ekonomi yaitu GDP perkapita, FDI dan Kualitas institusi diukur melalui 6 indikator berdasarkan world government indicators meliputi Control of Corruption (CC), Voice and Accountability (VA), Government Effectiveness (GE), Rule of Law (ROL), Political Stability (PS), Regulatory Quality (RQ) bersumber dari World Bank. Temuan – Hasil penelitian menunjukkan bahwa Regulatory quality, Control of corruption, Voice and accountability, dan Government effectiveness berpengaruh signifikan terhadap pertumbuhan ekonomi di negara ASEAN. Selain itu, FDI juga berpengaruh signifikan terhadap pertumbuhan ekonomi di negara ASEAN. Implikasi – Pemerintah meningkatkan kualitas institusi dan kemudahan dalam investasi untuk meningkatkan pertumbuhan ekonomi. Orisinalitas – Penelitian ini berkontribusi terhadap kebijakan pembangunan ekonomi terkait kelembagaan ekonomi dan investasi.